2004
DOI: 10.1115/1.1985442
|View full text |Cite
|
Sign up to set email alerts
|

Application of Constrained H∞ Control to Active Suspension Systems on Half-Car Models

Abstract: This paper formulates the active suspension control problem as disturbance attenuation problem with output and control constraints. The H∞ performance is used to measure ride comfort such that more general road disturbances can be considered, while time-domain hard constraints are captured using the concept of reachable sets and state-space ellipsoids. Hence, conflicting requirements are specified separately and handled in a nature way. In the framework of Linear Matrix Inequality (LMI) optimization, constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Optimal frequency response plots were obtained by using the "Hamming" window setting, a segment length of N/100 (where N is the total number of samples) and a percentage overlap of 2 14 (The MathWorks, Inc., 2001). Frequency responses are plotted for Δ=±30% variation in the linear, nonlinear, and asymmetric damping coefficients in Section 5.1 (Chen et al, 2005). The time domain response plots for the AVSS and PVSS traversing over a sinusoidal bump road input disturbance are given in Section 5.2 (Chen et al, 2005).…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimal frequency response plots were obtained by using the "Hamming" window setting, a segment length of N/100 (where N is the total number of samples) and a percentage overlap of 2 14 (The MathWorks, Inc., 2001). Frequency responses are plotted for Δ=±30% variation in the linear, nonlinear, and asymmetric damping coefficients in Section 5.1 (Chen et al, 2005). The time domain response plots for the AVSS and PVSS traversing over a sinusoidal bump road input disturbance are given in Section 5.2 (Chen et al, 2005).…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Frequency responses are plotted for Δ=±30% variation in the linear, nonlinear, and asymmetric damping coefficients in Section 5.1 (Chen et al, 2005). The time domain response plots for the AVSS and PVSS traversing over a sinusoidal bump road input disturbance are given in Section 5.2 (Chen et al, 2005).…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of the fuzzy logic active suspension was compared to a passive suspension and to a benchmark active suspension. A large number of different arrangements from semi active to fully active schemes have been investigated [5,6,7,8,9] In[10 , a complete set of constraints was derived on the road and load disturbance response transfer functions and results on the choice of sensors needed to achieve these degrees of freedom independently were obtained for the quarter car model The generalization of these results to half and full car models was then presented in [11] In [12], it was shown that the road and load disturbance responses cannot be adjusted independently for any passive suspension applied to a quarter car model In this paper, an automatic suspension system for a quarter car is considered and a fuzzy logic controller is designed when the vehicle is experiencing any road disturbance, the vehicle body should not have large oscillations, and the oscillations should dissipate quickly The road disturbance is simulated by a step input as a soft road test and rough road as a simulated to real way and the distance between the body mass and simulation mass is output of the system…”
Section: Introductionmentioning
confidence: 99%